Competitive Behavior and its Relationship to Some Mental Skills of Football Players - حبارة محمد; امان الله رشيد; بن سالم سالم (sports creativity, 2025)
The present study aimed to identify the type of relationship that exists between competitive behavior and some mental skills during a sports match. Where we used the descriptive method on 72 players distributed among four football teams in the state of M'sila; After applying the two study tools, the Competitive Behavior Scale and the Mental Skills Scale, that Muhammad Hassan Allawi translated into Arabic, the study concluded that there are correlative relationships between competitive behavior and the skill of focusing attention, mental perception and relaxation skill.